Ordered changes in histone modifications at the core of the Arabidopsis circadian clock - Malapeira, Jordi (National Academy of Sciences, 2012)
Circadian clock function in Arabidopsis thaliana relies on a complex network of reciprocal regulations among oscillator components. Here, we demonstrate that chromatin remodeling is a prevalent regulatory mechanism at the core of the clock. The peak-to-trough circadian oscillation is paralleled by the sequential accumulation of H3 acetylation (H3K56ac, K9ac), H3K4 trimethylation (H3K4me3), and H3K4me2. Inhibition of acetylation and H3K4me3 abolishes oscillator gene expression, indicating that both marks are essential for gene activation. Mechanistically, blocking H3K4me3 leads to increased clock-repressor binding, suggesting that H3K4me3 functions as a transition mark modulating the progression from activation to repression. The histone methyltransferase SET DOMAIN GROUP 2/ARABIDOPSIS TRITHORAX RELATED 3 (SDG2/ATXR3) might contribute directly or indirectly to this regulation because oscillator gene expression, H3K4me3 accumulation, and repressor binding are altered in plants misexpressing SDG2/ATXR3. Despite divergences in oscillator components, a chromatin-dependent mechanism of clock gene activation appears to be common to both plant and mammal circadian systems.